Novel Role of the Antimicrobial Peptide LL-37 in the Protection of Neutrophil Extracellular Traps against Degradation by Bacterial Nucleases - Neumann, Ariane (S. Karger AG, 2014)
Neutrophil extracellular traps (NETs) have been described as a fundamental innate immune defence mechanism. They consist of a nuclear DNA backbone associated with different antimicrobial peptides (AMPs) which are able to engulf and kill pathogens. The AMP LL-37, a member of the cathelicidin family, is highly present in NETs. However, the function of LL-37 within NETs is still unknown because it loses its antimicrobial activity when bound to DNA in the NETs. Using immunofluorescence microscopy, we demonstrate that NETs treated with LL-37 are distinctly more resistant to S. aureus nuclease degradation than nontreated NETs. Biochemical assays utilising a random LL-37-fragment library indicated that the blocking effect of LL-37 on nuclease activity is based on the cationic character of the AMP, which facilitates the binding to neutrophil DNA, thus protecting it from degradation by the nuclease. In good correlation to these data, the cationic AMPs human beta defensin-3 and human neutrophil peptide-1 showed similar protection of neutrophil-derived DNA against nuclease degradation. In conclusion, this study demonstrates a novel role of AMPs in host immune defence: beside its direct antimicrobial activity against various pathogens, cationic AMPs can stabilise neutrophil-derived DNA or NETs against bacterial nuclease degradation.